Kegiatan Pemuridan Bagi Jemaat GKSI Anugerah Padang Dalam Pertumbuhan Rohani - Febrianto Rompis; Mortan Sibarani; Ayu Lestari; Fernado Tambunan (Sekolah Tinggi Teologi Real Batam, 2023)
The purpose of this discipleship research is to improve the spirituality of the congregation that is still very lacking in order to grow more mature in spirituality, the introduction of the creator, namely the Lord Jesus Christ and between the congregations of GKSI Anugerah Padang, as well as to be able to respond and respect each other in their opinions. The problem that often occurs is the high ego of each other which makes the congregation divided, because faith in Jesus Christ as the Head of the Church has not been firmly and properly possessed, besides that attachment and kinship have also not been felt closely and intimately because they rarely participate in training and coaching series outside of worship hours. The congregation meets only at Sunday worship, so some stop following the discipleship and leave the church. The method used is a lecture by following discipleship and taking part in delivering God's Word, each participant is required to follow each given session. The results were very encouraging, there was a thank you from the participants for having the opportunity to participate in coaching with various new understandings from him, in Sunday services also not too late to arrive, participants had arrived at the Church long before the service began. The discipleship guide took a wise attitude in interrupting the discipleship because finally the congregation gradually lowered each other's egos, this is one of the references for holding discipleship at the Faithful Indonesian Christian Church Anugerah Padang.Keywords: GKSI; literacy: discipleship; spiritual growth AbstrakTujuan penelitian pemuridan ini adalah untuk meningkatkan kerohanian jemaat yang masih sangat kurang agar bertumbuh lebih dewasa dalam kerohanian, pengenalan akan Sang pencipta yaitu Tuhan Yesus Kristus dan antar jemaat GKSI Anugerah Padang, juga agar bisa saling menyikapi dan menghargai satu sama lain dalam berpendapat. Permasalahan yang sering terjadi adalah tingginya ego satu sama lain yang membuat terpecah belahnya jemaat, sebab iman kepada Yesus Kristus sebagai Kepala Gereja belum dimiliki dengan kokoh dan benar, selain itu keterikatan dan kekerabatan juga belum dirasakan karib dan akrab karena jarang mengikuti seri pelatihan dan pembinaan di luar jam ibadah. Jemaat bertemu hanya pada ibadah minggu saja, sehingga ada yang berhenti mengikuti pemuridan serta keluar dari gereja. Metode yang digunakan adalah ceramah dengan mengikuti pemuridan dan mengambil bagian dalam menyampaikan Firman Tuhan, tiap peserta wajib mengikuti tiap sesi yang diberikan. Hasilnya sangat menggembirakan, ada ucapan syukur yang terucap dari peserta karena memperoleh kesempatan mengikuti pembinaan dengan berbagai pemahaman baru darinya, dalam kebaktian-kebaktian minggu juga tidak terlambat lagi datang, peserta telah tiba di Gereja jauh sebelum kebaktian dimulai. Pembimbing pemuridan mengambil sikap bijak dalam menyeselaikan pemuridan tersebut karena akhirnya jemaat sedikit demi sedikit saling menurunkan egonya, hal inilah yang menjadi salah satu acuan diadakannya pemuridan di Gereja Kristen Setia Indonesia Anugerah Padang.Kata Kunci: GKSI; literasi: pemuridan; pertumbuhan rohani